Bacteriophage as an Alternative to Antibiotics Promotes Growth Performance by Regulating Intestinal Inflammation, Intestinal Barrier Function and Gut Microbiota in Weaned Piglets - Zeng, Yongdi; Wang, Zirui; Zou, Tiande; Chen, Jun; Li, Guanhong; Zheng, Liuzhen; Li, Shuo; You, Jinming (Frontiers in Veterinary Science, 2021)
This study aimed to investigate the effects of dietary bacteriophage supplementation on growth performance, intestinal morphology, barrier function, and intestinal microbiota of weaned piglets fed antibiotic-free diet. A total of 120 weaned piglets were allotted to 4 dietary treatments with 5 pens/treatment and 6 piglets/pen in a 21-d feeding trial. The 4 diets were added with antibiotics (25 mg/kg quinocetone and 11.25 mg/kg chlortetracycline), 200, 400, or 600 mg/kg bacteriophage in the antibiotic-free basal diet, respectively. There was no difference for growth performance and all measured indices of serum and intestinal tissues between 200 mg/kg bacteriophage group and the control group with antibiotics (P > 0.05). More importantly, compared with the control diet, dietary 400 mg/kg bacteriophage inclusion increased ADG and ADFI, and decreased F/G and diarrhea incidence of weaned piglets (P < 0.05). Also, piglets fed 400 mg/kg bacteriophage had elevated VH in jejunum and ileum, reduced CD in jejunum and ileum, and elevated VH/CD in duodenum, jejunum and ileum (P < 0.05). Piglets fed 400 mg/kg bacteriophage had lower IL-1β and TNF-α, and higher IL-10 concentration in serum, and higher sIgA, ITF, and TGF-α content in the ileal mucosa (P < 0.05). Besides, dietary addition with 400 mg/kg bacteriophage decreased the D-lactate concentration and DAO activity in serum, and increased the relative mRNA expression of ZO-1, Claudin-1, Occludin, TLR2, TLR4 and TLR9, as well as the relative protein expression of Occludin in the jejunum (P < 0.05). However, the growth performance and all analyzed parameters in serum and intestinal tissues were not further improved when piglets fed 600 vs. 400 mg/kg bacteriophage (P > 0.05). MiSeq sequencing analysis showed that bacteriophage regulated the microbial composition in caecum digesta, as indicated by higher observed_species, Chao1, and ACE richness indices, as well as the relative abundance of some beneficial bacterial species, such as Firmicutes, Bacteroidetes, Tenericutes, and Ruminococcaceae (P<0.05). Collectively, 400 mg/kg bacteriophage can be used as an antibiotics alternative for promoting the growth of weaned piglets. The underlying mechanism is associated with a positive effect of bacteriophage on intestinal inflammation, intestinal barrier function and gut microbiota in weaned piglets.